Comparison of Aerodynamic Effects on the Commonwealth Advisory Aeronautical Research Council (CAARC) Tall Building Model Tested in Two Wind Tunnel Laboratories - Yuhao Zhu; Xu Zhou; Yong Chen; Chenyan Ma; Lingjun Wang; Chaorong Zheng; Bowen Yan (Applied Sciences)
Wind tunnel test results can be influenced by various factors such as the blockage ratio and scaling ratio. These factors may introduce errors in the experimental outcomes, impacting the accuracy and reliability of the data obtained. This study quantitatively assesses consistency and identifies uncertainty sources to enhance result uniformity across various wind tunnel laboratories. This study conducted a systematic comparison between different wind tunnels in terms of rigid model pressure measurement wind tunnel experiments on the same Commonwealth Advisory Aeronautical Research Council (CAARC) standard tall building model. The study analyzes and discusses the results of mean and root-mean-square (RMS) wind pressure coefficients, peak factors, extreme wind pressure coefficients, probability density distributions, and base overturning force coefficients. The results indicated that in the open-circuit wind tunnel laboratory, the mean wind pressure coefficient is underestimated in the positive pressure region and overestimated in the negative pressure region. This is due to the static pressure which significantly decreases the streamwise direction within the test section, and the difference in static pressure is logarithmically proportional to the mean wind speed. Additionally, dynamic pressure is uniformly distributed along the test section axis. The inaccurate measurement of static pressure leads to these results. To address this issue, an indirect measurement method was employed to correct the static pressure results and reduce the error in the mean wind pressure coefficient to within 10%. Furthermore, differences in turbulence integral scale result in an error of up to 16% in the RMS wind pressure coefficient. Therefore, when conducting rigid model pressure measurement wind tunnel experiments, especially in open-circuit wind tunnel laboratories, careful consideration should be given to the influence of static pressure drop and integral length scale of turbulence.